Embryonic Stem Cells Recent Advances in Pluripotent Stem Cell-Based Regenerative Medicine - Atwood, Craig (IntechOpen, 2011)
Pluripotent stem cells have the potential to revolutionise medicine, providing treatment options for a wide range of diseases and conditions that currently lack therapies or cures. This book describes recent advances in the generation of tissue specific cell types for regenerative applications, as well as the obstacles that need to be overcome in order to recognize the potential of these cells.